PENGARUH STRATEGI PEMASARAN TERHADAP LOYALITAS KONSUMEN PADA GIANT SUPERMARKET (PT. HERO SUPERMARKET TBK) DI BANDAR LAMPUNG - Yudiana Sari (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
The object of this research is Giant Supermarket (PT Hero Supermarket Tbk) in Bandar Lampung. Giant is one of the largest retail networks in Indonesia. The problem studied was to find out the effect of marketing strategies on consumer loyalty at Giant Supermarket (PT. Hero Supermarket Tbk) in Bandar Lampung because of consumer loyalty at the Giant Supermarket (PT. Hero Supermarket Tbk) which declined. The research method used in this study is library research and field research conducted by directly examining Giant Supermarkets (PT Hero Supermarket Tbk) in Bandar Lampung related to marketing strategies and their influence on consumer loyalty at Giant Supermarket (PT. Hero Supermarket Tbk) in Bandar Lampung. The results showed that the matrix analysis of IFAS and EFAS resulted in an analysis of the company's internal factors in the marketing strategy of Giant Supermarket (PT Hero Supermarket Tbk) in Bandar Lampung, which became the main force, namely promotion carried out by the company with a total value of 0.4662 and the main disadvantage is that famous brands still dominate with a total value of 0.1200. While the company's external factors in the marketing strategy of PT Giant Supermarket (PT Hero Supermarket Tbk) in Bandar Lampung, which is the main opportunity, is an increase in the population with a total value of 0.4235 and the company's main threat is the number of competing companies with a total value of 0.1582 . External internal matrix analysis (IE) Giant Supermarkets (PT Hero Supermarket Tbk) In Bandar Lampung are in the V cell position, thus implementing a strategy of maintaining and maintaining consumers (high consumer loyalty). Keywords: Strategy, Marketing, Loyalty, Consumers, IFAS, EFAS